Fostering Environmental Literacy and Creativity in Biology Education: A Systematic Review of Place-Based Learning in Conservation Areas - M Ikhsan Al Ghazi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Biology education currently faces a significant challenge in transforming cognitive biodiversity knowledge into added value for national development. The inability of pre-service teachers to integrate scientific data with creative solutions has resulted in low levels of applicable environmental literacy. This study aims to identify the potential and strategies for fostering environmental literacy and creativity among students through a systematic review of place-based learning in conservation areas. The method employed is a Systematic Literature Review (SLR), analyzing reputable scientific articles and utilizing bibliometric visualization through VOSviewer software to map research gaps. The results indicate a clear dichotomy between the mastery of ecological theory and students' creative capacity. Network analysis reveals that environmental literacy has been dominated by conventional waste management issues and remains isolated from creative problem-solving aspects and conservation area contexts. The conclusion of this study emphasizes that conservation areas, such as ecotourism sites, play a crucial role as living laboratories to bridge this gap. These findings serve as an empirical foundation for developing more structured project-based experiential learning models. In-depth identification of students' environmental literacy and creativity in the field is required as an initial step to prepare future educators capable of engineering solutions to local biological crises while contributing to the national creative industry